How structured and unstructured sport activities aid the development of expertise in volleyball players - Coutinho, P.; Mesquita, I.; Davids, K.; Fonseca, A. M.; Côté, J. (Psychology of Sport and Exercise, 2016)
This study sought to analyse self-reported perceptions of how the nature of sport activities undertaken by volleyball players aided their development. Thirty highly skilled and thirty less skilled players participated in retrospective interviews to identify the nature of activities undertaken in their developmental pathways. All players reported having an early-diversified sport involvement with participation in both structured and unstructured activities. Highly skilled players differed from less skilled players by having accumulated more hours of structured sport activities, some of which were undertaken with older peers. Furthermore, highly skilled players specifically highlighted the value of their involvement in particular unstructured activities with older peers and recognized their importance for expertise achievement. These findings illustrate the importance of considering the role of unstructured (in addition to structured) sport activities in the development of expertise in volleyball. Further work is needed to verify the generality of the findings to other sports.